Exploring the Historical Dissemination and Contemporary Resurgence of Monkeypox: A Comprehensive Examination of its Evolution, Global Impact, and Treatment Approaches - Sultana, Madiha; Verma, Tushar; Jose, Anju; Ramesh, Swetha; Singh, Sonia (International Journal of Pharmaceutical Investigation, 2026)
Monkeypox, an Orthopoxvirus genus zoonotic ailment, has resurfaced as a global public health issue, with outbreaks in 2022 and 2024 highlighting alterations in its epidemiology and transmission dynamics. This narrative synthesis amalgamates data from historical outbreaks, recent research, and official health documents to scrutinize the evolving epidemiological trends, clinical presentations, and current treatment and prevention strategies for monkeypox. Analysis indicates a notable demographic shift in the 2024 outbreak, with a rise in cases among children, healthcare professionals, and immunosuppressed individuals. Non-sexual transmission has emerged as a significant mode of infection in specific regions, particularly in areas affected by humanitarian crises. Progress in diagnostics, antiviral medications like tecovirimat, and vaccines such as JYNNEOS has substantially enhanced disease management. The resurgence of monkeypox underscores the imperative for comprehensive surveillance, fair vaccine distribution, and targeted public health measures to combat emerging zoonotic hazards.
Keywords: Mpox; Orthopoxvirus; Lymphadenopathy; Tecovirimat.